2017
DOI: 10.3928/23258160-20161219-02
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Childhood Obesity

Abstract: CT increases in childhood obesity. Findings revealed that adiposity causes a significant increase in CT, and it may be related to ocular complications. [Ophthalmic Surg Lasers Imaging Retina. 2017;48:10-17.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 41 publications
3
31
0
1
Order By: Relevance
“…Previous studies have shown that the choroidal thickness is higher in patients with BMI between 18-24 compared to those with BMI < 18.5 (384 ± 102 μm versus 378 ± 86 μm; p<0.01) [18]. Similarly, studies in obese women and children have shown that choroidal thickness is higher in patients with obesity compared to healthy control population [30,31]. In our study, we also observed higher choroidal thickness values in participants with obesity compared to healthy controls (Table 3), though it did not reach statistical significance.…”
Section: Plos Onementioning
confidence: 87%
“…Previous studies have shown that the choroidal thickness is higher in patients with BMI between 18-24 compared to those with BMI < 18.5 (384 ± 102 μm versus 378 ± 86 μm; p<0.01) [18]. Similarly, studies in obese women and children have shown that choroidal thickness is higher in patients with obesity compared to healthy control population [30,31]. In our study, we also observed higher choroidal thickness values in participants with obesity compared to healthy controls (Table 3), though it did not reach statistical significance.…”
Section: Plos Onementioning
confidence: 87%
“…This chronic inflammation also has the potential to produce changes in the retina and macular layer (20). Indeed, previous MetS: metabolic syndrome studies have shown that obesity reduces the thickness of the retinal nerve fiber layer in children and affects choroid tissue (21,22,23). Some studies have shown that obesity leads to changes in the macular layers in children.…”
Section: Discussionmentioning
confidence: 99%
“…Koroid kalınlık değişimine neden olan çok sayıda metabolik hastalık vardır. Egzersiz, gebelik, erkek cinsiyet, sildenafil kullanımı, prediyabetik retinopati, çocukluk çağı obesitesinin koroid kalınlığını artırdığı bildirilmiştir (12)(13)(14)(15)(16)(17) . Konjestif kalp yetersizliği, karotis stenozu, sigara, kahve, ileri yaş, çocuklarda demir eksikliği anemisi, diyabetik makülar ödem ve proliferatif diyabetik retinopatinin eşlik ettiği diyabetin koroid kalınlığını azalttığı bildirilmiştir (7,(18)(19)(20)(21)(22) .…”
Section: Discussionunclassified